Mixed Boundary Value Problem for a Monotone Equation with a Lower Order Term and Point Sources on the Right Side - O. А. Zadvornov; G. O. Trifonova (Учёные записки Казанского университета: Серия Физико-математические науки)
The existence of a solution to the mixed boundary value problem for a quasilinear equation with a lower order term and point sources on the right side was proved. The solution was obtained in an additive form, and the features associated with point sources were clearly highlighted. The approach used in the proof can serve as a basis for a method of solving this type of problem.